SlMYC2 interacted with the SlTOR promoter and mediated JA signaling to regulate growth and fruit quality in tomato - Zhang, Yujiao; Xing, Hongyun; Wang, Haoran; Yu, Lan; Yang, Zhi; Meng, Xiangnan; Hu, Pengpeng; Fan, Haiyan; Yu, Yang; Cui, Na (Frontiers in Plant Science, 2022)
Tomato (Solanum lycopersicum) is a major vegetable crop cultivated worldwide. The regulation of tomato growth and fruit quality has long been a popular research topic. MYC2 is a key regulator of the interaction between jasmonic acid (JA) signaling and other signaling pathways, and MYC2 can integrate the interaction between JA signaling and other hormone signals to regulate plant growth and development. TOR signaling is also an essential regulator of plant growth and development. However, it is unclear whether MYC2 can integrate JA signaling and TOR signaling during growth and development in tomato. Here, MeJA treatment and SlMYC2 overexpression inhibited the growth and development of tomato seedlings and photosynthesis, but increased the sugar–acid ratio and the contents of lycopene, carotenoid, soluble sugar, total phenol and flavonoids, indicating that JA signaling inhibited the growth of tomato seedlings and altered fruit quality. When TOR signaling was inhibited by RAP, the JA content increased, and the growth and photosynthesis of tomato seedlings decreased, indicating that TOR signaling positively regulated the growth and development of tomato seedlings. Further yeast one-hybrid assays showed that SlMYC2 could bind directly to the SlTOR promoter. Based on GUS staining analysis, SlMYC2 regulated the transcription of SlTOR, indicating that SlMYC2 mediated the interaction between JA and TOR signaling by acting on the promoter of SlTOR. This study provides a new strategy and some theoretical basis for tomato breeding.